KEHILANGAN HARA PADA TANAH MIRING HUTAN PRIMER DI TAMAN NASIONAL DUMOGA - BONE, SULAWESI UTARA - HERWINT SIMBOLON (Research Center for Biology-Indonesian Institute of Sciences, 1988)
H. SIMBOLON 1988.Soil nutrients loss on a slope in the primary forest of Dumoga-Bone Nationat Park.North Sulawesi. Berita Biologi 3(8): 413 -417.The lost of soil nutriens in the lowland primary forest have beer studied in Lombongo,Dumoga-Bone National Park (North Sulawesi).The forest was dominated by Pometia pinnata with 25.71% of relative basal area.The forest canopy was built up by 368 trees per ha and the soil surface was covered by 353.92 g per m of litterfall (mean of fresh weight).The soil-and litterfall nutrient status of the study plots was less than that of the other primary tropical rain forests.Even though the soils were fully covered by litterfall, the erosion and leaching processes were still occurring.The leaching rate of the soil nutrients was 3.26% on C(the lowest rate) and 14.46% on P2Q5 (the highest rate),but no significant decrease on N was observed.